Bidirectional measurement for Brillouin optical correlation domain analysis - Jeong, Ji Ho; Lee, Kwanil; Song, Kwang Yong; Jeong, Je-Myung; Lee, Sang Bae (OPTICAL SOC AMER, 2012)
We propose and experimentally demonstrate a bidirectional measurement for Brillouin optical correlation domain analysis as a novel and simple way of the performance enhancement. Brillouin gain and loss spectra of two adjacent correlation peaks are simultaneously and independently analyzed by applying midpoint attenuation in a fiber under test, which doubles both the speed and the range of the distributed measurement. (c) 2012 Optical Society of America
Keywords: DISTRIBUTED STRAIN-MEASUREMENT; ORDER SPATIAL-RESOLUTION; FIBER; SENSOR; SUPPRESSION; SCATTERING